Subjective Expectations and Demands for Contraception - Grant Miller; Áureo de Paula; Christine Valente (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2020)
One quarter of married, fertile-age women in Sub-Saharan Africa report not wanting a pregnancy and yet do not use contraceptives. To study this issue, we collect detailed data on women's subjective probabilistic beliefs and estimate a structural model of contraceptive choices. Our results indicate that costly interventions like eliminating supply constraints would only modestly increase contraceptive use. Alternatively, increasing partners' approval of methods, aligning partners' fertility preferences with women's beliefs about pregnancy risk absent contraception have the potential to increase use considerably. Results from a before/after experiment testing this last finding are highly consistent with the structural estimates.
Keywords: J13; J16; D83; 330; Contraception; Probabilistic Beliefs; Mozambique